Effect of different flooring condition on growth performance and disease incidence of preweaned Frieswal calves (Indian Journal of Animal Production and Management, 2024)
The present study was carried in the herd of Frieswal crossbred calves. Thirty Frieswal calves (15 male  and 15 female) were included in the experiment at 3 days of their birth (after colostrum feeding). They  were distributed into 3 groups (3 floor types with 10 calves (5 male + 5 female) in each group): Concrete  floor, Concrete floor with straw beddings and Earthen (Kachha) floor. In general, Average daily gain (ADG)  showed an increasing trend with the advancement of age. At 9th and 10th week of age i.e., just after stopping  of milk feeding ADG decreased however, in subsequent weeks, calves regained their weight gain. From  fourth fortnight onward the gains in heart girth were significantly higher (P
Keywords: Average daily gain; Disease incidence; Frieswal calves; Heart girth and Height at withe